The Use of English Movie to Enhance Tenth Grade Students' Pronunciation at SMA Angkasa 2, East Jakarta - Rayasa, Reggy (JET (Journal of English Teaching), 2018)
This study aims at developing students’ pronunciation skills by using English movies as a teaching media and investigating the students’ perception of the use English movie in learning pronunciation. To attain the objectives, a two-cycled action research was conducted to 35 tenth graders at SMA Angkasa 2, East Jakarta in March to May 2017. Data were collected using test, some observation sheets, and a questionnaire. The results revealed that the movies developed the students’ pronunciation skills. Their poor pronunciation (indicated by the pretest mean score of 48,11) developed after participating in Cycle I (mean score, 62.5) and developed higher after Cycle II (mean score, 76.08). Along with the increase of frequency of watching the movies and the researcher’s improvement in facilitating the actions as well, the students’ enthusiasm and involvement in the actions keep on increasing. It was concluded that using use movies as teaching media is effective to develop students' pronunciation skills. EFL teachers are, therefore, recommended to use movies as an alternative media to develop students' pronunciation skills. Further studies are recommended to carry out experimental studies to see the degree of effectiveness of using movies in pronunciation teaching to senior high school students.